Formação e sexualidade: um estudo a partir dos relatos dos estudantes de difererentes cursos de Psicologia - Senem, Cleiton José [UNESP] (2015)
Sexuality is a fundamental dimension in the human being's life, from birth to old age. It is inherent in human nature, presenting different manifestations throughout history and receiving several forms and meanings. Sexuality is constituted of imbricate dimensions: biological, cultural, and psychological. When we observe the different ways people have lived sexuality thoughout history, it is possible to identify matriarchal and patriarchal models, moments of greater openness and freedom, as well as phases of repression, fear, and mistrust. Sexuality is the object of several sciences and Psychology also, since these professionals work directly with this issue in all their activities, in the clinic, organization, school, and community. Therefore, they must be prepared to openly address the issues concerning such topic, with no prejucice, developing actions that are constructive, critical, and systematic and helping people and groups to reflect on this issue. Thus, the purpose of this study was to investigate the reports of Psychology students on sexuality, considering the implications of the course on their personal and professional training. The participants of the research were 11 fourth-year Psychology students (8th semester), from three different institutions, who answered a semi-structured questionnaire. The results indicate that students have a wide and complex understanding of sexuality, considering its biological, cultural and psychological dimensions. At the same time, the reproduction of a patriarchal conception of sexuality could be identified both in the answers provided by men and women. A different of perception was found among the different institutions: while participants of the private universities showed themselves to be more conservative, the participants of the public university showed themselves to be more liberal. It is also possible to identify that, although all courses approach the topic in its formative process...